2012
DOI: 10.1186/1745-6215-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adherence to the CONSORT statement for quality of reports on randomized controlled trial abstracts from four high-impact general medical journals

Abstract: Background The extended Consolidated Standards of Reporting Trials (CONSORT) Statement for Abstracts was developed to improve the quality of reports of randomized controlled trials (RCTs) because readers often base their assessment of a trial solely on the abstract. To date, few data exist regarding whether it has achieved this goal. We evaluated the extent of adherence to the CONSORT for Abstract statement for quality of reports on RCT abstracts by four high-impact general medical journals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 29 publications
9
107
3
1
Order By: Relevance
“…Because reporting quality and methodological quality of controlled trials are two different dimensions (for example, well-conducted trials may be reported poorly) (Huwiler-Müntener et al 2002), this should be evaluated in different ways. Our findings were consistent with those of previous studies in other fields of health research that reporting quality of the abstracts was suboptimal (Berwanger et al 2009;Chhapola et al 2016;Ghimire et al 2012;Guo & Iribarren 2014;Kiriakou et al 2014;Seehra et al 2013). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Because reporting quality and methodological quality of controlled trials are two different dimensions (for example, well-conducted trials may be reported poorly) (Huwiler-Müntener et al 2002), this should be evaluated in different ways. Our findings were consistent with those of previous studies in other fields of health research that reporting quality of the abstracts was suboptimal (Berwanger et al 2009;Chhapola et al 2016;Ghimire et al 2012;Guo & Iribarren 2014;Kiriakou et al 2014;Seehra et al 2013). …”
Section: Discussionsupporting
confidence: 93%
“…Randomization, one of the most important items in this domain, is an experimental design tool used for reducing bias, and it is used for categorizing trials into RCTs and non-RCTs. Reporting quality of abstracts in medical literature is usually performed in RCTs only (Cui et al 2014;Ghimire et al 2012;Guo & Iribarren 2014;Hua et al 2015;Kiriakou et al 2014) because non-RCTs are not widely acceptable due to high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ursprüng-lich für die Publikation von 2 Parallelgruppen entwickelt, wurden CONSORTErweiterungen für weitere randomisierte Studiendesigns wie z. B. Cluster-randomisierte Studien [3], "Non-inferiority"-und Äquivalenzstudien [13], aber auch Vorgaben für die Publikation von Abstracts [8] Fachzeitschriften das Befolgen des CON-SORT-Statements zunehmend befürwor-ten, zeigten neuere Untersuchungen, dass die Qualität des Berichtens von medizinischen Studien weiterhin verbesserungsbedürftig ist [6,7,14]. Untersuchungen der Studienberichterstattung in den TopAnästhesie-und Top-IntensivmedizinJournals ergaben eine nur ca.…”
Section: Consort-statement Für Randomisierte Kontrollierte Studienunclassified